2021
DOI: 10.1002/slct.202103003
|View full text |Cite
|
Sign up to set email alerts
|

Pd(II)‐Catalyzed Chelation‐Induced C(sp2)‐H Acylation of (Hetero)Arenes Using Toluenes as Aroyl Surrogate

Abstract: In the last few years, transition‐metal‐catalyzed chelation‐controlled ortho‐acylation utilizing methyl arene as the acyl partner has emerged as a powerful technique to achieve diverse complexity with diaryl ketone skeleton contrast to the traditional cross‐coupling/Friedel‐Craft reaction. Diaryl ketones are a significant building block that exists in pharmaceuticals, agrochemicals, natural products, functional materials, and many other useful compounds. In this context, the up‐to‐date developments in Pd(II)‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 97 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Our group has recently reported the synthesis of a variety of 2-(hetero)­aroylpyrroles through a Pd­(II)-catalyzed acylation of pyrrole with aldehydes in the presence of an oxidant, using 2-methylpyridinyl and 2-pyrimidyl as directing groups . This radical C–H activation reaction is a good catalytic alternative to classical acylation methods (Friedel–Crafts, Vilsmeier–Haack, or Houben–Hoesch type acylation reactions), which minimizes the production of waste as it does not require the use of stoichiometric amounts of Lewis or protic acids. Thus, we had demonstrated that the use of 2-pyrimidinyl directing group led to C-2 metalation of pyrrole using Pd­(OAc) 2 as the pre-catalyst in toluene, which were acylated with aldehydes in the presence of TBHP as the oxidant and pivalic acid as the additive.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has recently reported the synthesis of a variety of 2-(hetero)­aroylpyrroles through a Pd­(II)-catalyzed acylation of pyrrole with aldehydes in the presence of an oxidant, using 2-methylpyridinyl and 2-pyrimidyl as directing groups . This radical C–H activation reaction is a good catalytic alternative to classical acylation methods (Friedel–Crafts, Vilsmeier–Haack, or Houben–Hoesch type acylation reactions), which minimizes the production of waste as it does not require the use of stoichiometric amounts of Lewis or protic acids. Thus, we had demonstrated that the use of 2-pyrimidinyl directing group led to C-2 metalation of pyrrole using Pd­(OAc) 2 as the pre-catalyst in toluene, which were acylated with aldehydes in the presence of TBHP as the oxidant and pivalic acid as the additive.…”
Section: Resultsmentioning
confidence: 99%